Existence of Multiple Positive Periodic Solutions for Second Order Differential Equations (Communications in Mathematical Research, 2021)
In this paper, we study the existence of multiple positive periodic solutionsfor the second order differential equation $$x''(t) + p(t)x' (t) + q(t)x(t) = f(t, x(t)).$$ By using Krasnoselskii fixed point theorem, we establish some criteria for the existence and multiple positive periodic solutions for this differential equation.